2018
DOI: 10.1007/s11557-018-1443-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortinarius sect. Riederi: taxonomy and phylogeny of the new section with European and North American distribution

Abstract: Cortinarius is one of the most species-rich genera of mushroom-forming fungi. Based on phylogenetic and morphological evidence, a new section, Cortinarius, sect. Riederi, is introduced. The taxonomy, phylogeny, ecology and distribution of mainly European but also including some North American taxa of this section are treated, which includes 9 species and two varieties). Of these, three taxa are described as new (C. burlinghamiae, C. pallidoriederi, and C. argenteolilacinus var. dovrensis). The sect. Riederi sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Cortinarius species have appeared widely distributed in the northern hemisphere in previous works (e.g. Garnica et al 2009, Harrower et al 2011, Niskanen et al 2012a, Cripps et al 2015, Liimatainen et al 2015, 2017, Brandrud et al 2018. The morphological features varied much within species.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Cortinarius species have appeared widely distributed in the northern hemisphere in previous works (e.g. Garnica et al 2009, Harrower et al 2011, Niskanen et al 2012a, Cripps et al 2015, Liimatainen et al 2015, 2017, Brandrud et al 2018. The morphological features varied much within species.…”
Section: Discussionmentioning
confidence: 87%
“…Recently developed molecular methods have promoted the Cortinarius taxonomy, especially concerning boreal forest species (e.g. Niskanen et al 2009, 2013, 2017, Dima et al 2016, Brandrud et al 2018. This study focused on a specific habitat, alluvial Salix thickets.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, evolutionary relationships remained mostly opaque, as is often the case in phylogenetic analysis including only one molecular marker, and very divergent sequences among taxa (e.g. Brandrud et al 2018;Garrido-Benavent et al 2019). The two Pakistani collections AST20 and MJ-15103 were genetically identical.…”
Section: Molecular Phylogenetic Analysesmentioning
confidence: 99%
“…Among them, the nuc rDNA ITS1-5.8S-ITS2 region has been found to be a suitable molecular marker for the correct identi cation of fungi by the consortium of international barcode (Seifert 2009;Schoch et al 2012;Schoch et al 2014). Several studies have found that ITS barcode can prove signi cantly effective in distinguishing Cortinarius species (Garnica et al 2016;Brandrud et al 2018). Molecular approach together with morphological analysis can signi cantly improve the accuracy in identi cation of such fungi.…”
Section: Introductionmentioning
confidence: 99%